Cassava and sweetpotato yield assessment in Malawi - Moyo, C.C.; Benesi, I.R.M.; Chipungu, Felistus P.; Mwale, C.H.L.; Sandifolo, V.S.; Mahungu, N.M. (African Journals Online, 2004)
Cassava (Manihot esculenta Crantz) and sweetpotato (Ipomoea batatas Lam) are important food and cash crops in Malawi. However, key information regarding varieties grown, sources of planting materials, post-harvest handling, utilisation and tuber yields is lacking. A study was, therefore, conducted to source this information. Farmers grow mostly local varieties of cassava with own gardens as the main source of planting materials. Several varieties of sweetpotato are grown with Kenya (SPN/O, bred in Tanzania) as the most popular. Sprouts from previous season\'s gardens are the main source of planting materials. Cassava and sweetpotato are grown for food and cash. However, in some area cassava stems are used for fuel wood. Most farmers do not store fresh cassava roots but process them into makaka, kanyakaska and kadonoska, or sell them fresh. Processing for sweetpotato is limited to boiling and roasting. Most farmers store sweetpotato, but this is constrained by the sweetpotato weevil damage and rotting. Root yield ranged from 13.1 to 31.4 t ha-1 for cassava, and 10.2 to 14.0 t ha-1 for sweetpotato. Except for Nkhata Bay, the yields of both crops were much lower than from research stations. Unavailability of acceptable improved varieties, high incidence of pests and diseases, and poor cultural practices are the main causes of low yields in the targeted areas.